Polymer electrolyte as well as preparation method and application thereof
By using polymer electrolytes of 1-azabicyclic[2.2.2]octane and its derivatives in lithium-ion batteries, a double-layer crosslinking network structure was formed, and the problem of insufficient safety performance of polymer solid electrolytes was solved, and the problem of achieving the Higher battery stability and safety.
Patent Information
- Application Number
- CN202411432997.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-17
AI Technical Summary
The lack of safety performance of polymer solid electrolytes in lithium-ion batteries limits their commercial applications.
Using polymer electrolytes containing 1-azabicyclic[2.2.2]octane and its derivatives, a two-layer polymer cross-linking network structure is formed through the combination of cross-linking polymer and plastic crystals, thereby improving electrochemical stability and Safety performance.
It significantly improves the safety performance, cycle retention rate and 3C rate discharge performance of lithium-ion batteries, reduces the interface impedance, and enhances the stability and safety of the battery.
Smart Images

Figure BDA0005084198570000111 
Figure BDA0005084198570000112 
Figure BDA0005084198570000261
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a polymer electrolyte, a preparation method thereof and an application thereof. Background Art
[0002] Lithium-ion batteries are one of the important technologies in the field of energy storage, with the advantages of high energy density, high operating voltage, fast response speed and long cycle life. In order to meet the growing demand for grid-level energy storage and modern electric vehicles, the development of lithium-ion batteries with higher energy density, lower cost, longer working life and better safety has become a key research topic in the field of energy storage.
[0003] Solid electrolytes have attracted the attention of a large number of researchers due to their advantages such as good energy storage stability, good chemical stability and long cycle life, and are considered to be extremely effective materials for improving battery energy density. Solid electrolytes are mainly divided into inorganic solid electrolytes, polymer solid electrolytes and composite solid electrolytes. Among them, the polymer solid electrolyte system still has many disadvantages, especially its safety performance, which limits the commercial application of solid electrolytes including polymer solid electrolytes in secondary batteries. Summary of the invention
[0004] In view of this, the technical problem to be solved by the present invention is to provide a polymer electrolyte, a preparation method thereof and an application thereof. The polymer electrolyte provided in this application can greatly improve the safety performance of lithium-ion batteries.
[0005] The present application provides a polymer electrolyte, comprising 1wt% to 90wt% of a cross-linked polymer, 0.01wt% to 50wt% of a plastic crystal and 0.01wt% to 20wt% of a lithium salt; the plastic crystal is selected from 1-azabicyclo[2.2.2]octane and its derivatives.
[0006] The polymer electrolyte provided in the present application includes a cross-linked polymer. The present application has no special restrictions on the cross-linked polymer, which can be formed by cross-linking and polymerization of double bond monomers under the action of a cross-linking agent to form a network structure. In some specific implementations, the cross-linked polymer is obtained by cross-linking and polymerization of a polymerized monomer, an initiator and a cross-linking agent.
[0007] In some specific implementations, the polymerizable monomers include but are not limited to vinylene carbonate, vinyl ethylene carbonate, vinyl carbonate, diethyl carbonate, triethylene glycol divinyl ether, methyl vinyl sulfone, ethyl vinyl sulfone, methyl methacrylate, pentafluoropropyl methacrylate, ethylene glycol dimethacrylate, propylene glycol dimethacrylate, n-butyl methacrylate, ethyl acrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, polyethylene oxide acrylate, polymethyl methacrylate, polyethylene glycol methyl ether methacrylate and polycyanoacrylate, etc., and may be one or more of them. When the polymerizable monomers are a composition of two or more, the present application has no special restrictions on the amount of each substance used, and those skilled in the art can select according to their needs. In some specific implementations, the polymerizable monomer is preferably at least one of methyl vinyl sulfone, vinyl ethylene carbonate, ethylene glycol dimethacrylate, triethylene glycol divinyl ether, ethyl vinyl sulfone, vinyl acetate or ethoxylated trimethylolpropane triacrylate, more preferably at least one of ethoxylated trimethylolpropane triacrylate or vinyl acetate.
[0008] In some specific implementations, the initiator includes but is not limited to azobisisobutyronitrile, azobisisoheptylnitrile, dimethyl azobisisobutyrate, benzoyl peroxide, lauroyl peroxide, isopropylbenzene hydroperoxide, tert-butyl hydroperoxide, methyl ethyl ketone peroxide, di-tert-butyl peroxide, lauroyl peroxide, diisopropylbenzene peroxide, N,N-dimethylcyclohexylamine, bis(2-dimethylaminoethyl) ether, triethylenediamine, triethylamine, N,N,N,N'-tetramethylalkylenediamine, N,N-dimethylbenzylamine, N,N-dimethylbutylamine, N,N -Dimethylhexadecylamine, N,N-diethylpiperazine, N,N-diethyl-2-methylpiperazine, N,N'-bis(α-hydroxypropyl)-2-methylpiperazine, triethanolamine, N,N-dimethylethanolamine, N,N-dimethylpyridine, (dimethylaminoethyl) ether, N-methylethylenediamine, dimethylformamide, triethyleneethylenediamine, methyldiethyleneglycolamine, triethylenediamine and hexamethyldisilazane, which can be one or more of them. When the initiator is a composition of two or more, the application has no special restrictions on the amount of each specific substance. In some specific implementations, the initiator is preferably at least one of azobisisobutyronitrile, dimethyl azobisisobutyrate, di-tert-butyl peroxide, methyl ethyl ketone peroxide, and lauroyl peroxide, and more preferably at least one of methyl ethyl ketone peroxide and azobisisobutyronitrile.
[0009] In some specific implementations, the crosslinking agent includes but is not limited to polyethylene glycol diacrylate, polyethylene glycol methacrylate, polyethylene glycol dimethacrylate, tetra(ethylene glycol) diacrylate, pentaerythritol tetraacrylate, pentaerythritol glycidyl ether, 1,4-pyrazine dicarboxaldehyde, 4,4'-biphenyl dicarboxaldehyde, 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether, γ-glycidyl ether oxygen silyl propyl sesquioxane, trimethylolpropane triglycidyl ether, trimethylolpropane propoxy ester triacrylate, trimethylolpropane triacrylate and pentaerythritol tetraacrylate, which can be one or more of them. When the crosslinking agent is a composition of two or more of them, the application has no special restrictions on the amount of each specific substance. In some specific implementations, the crosslinking agent is preferably at least one of polyethylene glycol diacrylate, polyethylene glycol methacrylate and trimethylolpropane propoxy ester triacrylate.
[0010] In some specific implementations, the mass ratio of the polymerization monomer, the initiator and the cross-linking agent is preferably 1-90:0.01-10:1-90, preferably 10-80:0.05-10:1-50, and more preferably 18-24:0.1-10:1-3.
[0011] In some specific implementations, the content of the cross-linked polymer in the polymer electrolyte is 1 wt% to 90 wt%, preferably 20 wt% to 80 wt%, more preferably 30 wt% to 75 wt%, and most preferably 40 wt% to 70 wt%. The cross-linked polymer as a matrix helps to improve mechanical properties on the one hand, and can make the plastic crystals evenly distributed on the other hand, further improving ionic conductivity.
[0012] The polymer electrolyte provided in the present application includes plastic crystals, which is the abbreviation of plastic crystals and is a class of substances with unique properties. In some specific implementations, the plastic crystals are selected from 1-azabicyclo[2.2.2]octane and its derivatives, which are plastic crystals doped with ionic salts. The applicant has found that compared with other types of plastic crystals, 1-azabicyclo[2.2.2]octane and its derivatives can be homogenized with the polymer, thereby inhibiting the growth of dendrites and greatly improving the safety performance of polymer solid-state batteries. At the same time, 1-azabicyclo[2.2.2]octane and its derivatives can reduce the side reactions between the active substances and the electrodes, improve the short-circuit resistance of the battery, and further enhance the safety performance of the battery. In addition, the defects in the structure of 1-azabicyclo[2.2.2]octane and its derivatives can improve the rate of lithium ion migration at the interface, and the electron-rich groups in the polymer chain segments can undergo strong complexation with lithium ions, promoting the dissociation of lithium salts to produce more free Li + , thereby effectively improving Li +Migration rate in the battery; the quaternary ammonium cation main chain of 1-azabicyclo[2.2.2]octane and its derivatives is positively charged, which can generate ion-dipole interaction forces with polymer chain segments, thereby inhibiting the movement of polymer chain segments and further improving the electrochemical stability of the polymer solid electrolyte.
[0013] In some specific implementations, the crystal shaping agent includes, but is not limited to, 1-azabicyclo[2.2.2]octane perchloric acid, (R)-(-)-1-azabicyclo[2.2.2]octane-3-ol perchloric acid, (S)-(+)-1-azabicyclo[2.2.2]octane-3-ol perchloric acid and 1-azabicyclo[2.2.2]octane-3-ol perchloric acid, and may be one or more of them. When the crystal shaping agent is a combination of two or more substances, the present application has no special restrictions on the amount of each specific substance.
[0014] In some specific implementations, the content of the plastic crystal in the polymer electrolyte is 0.01wt% to 50wt%, preferably 1wt% to 45wt%, more preferably 10wt% to 40wt%, and most preferably 15wt% to 35wt%. 1-Azabicyclo[2.2.2]octane and its derivatives can produce conjugation with the end of the polymer precursor segment, control the reaction rate of polymer polymerization, reduce the polymer crystallinity, and make the polymerization process more gentle, so that the generated polymer solid electrolyte is more uniform and has better contact with the electrode, further adjusting the lithium ion transport performance and mechanical properties of the polymer solid electrolyte, and constructing a good positive electrode-electrolyte interface and a negative electrode-electrolyte interface, reducing the interface impedance between the two, and realizing a long cycle of the full battery.
[0015] The polyelectrolyte provided in the present application includes a lithium salt, and the lithium salt includes but is not limited to lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonic acid)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(oxalate)borate, lithium difluorooxalateborate, lithium chloride, lithium iodide, lithium bis(fluorosulfonyl)imide and lithium hexafluoroarsenate, etc., which can be one or more of them. When the lithium salt is a composition of two or more, the present application has no special restrictions on the content of each specific substance. In some specific implementations, the lithium salt is preferably at least one of lithium perchlorate, lithium bis(oxalate)borate and lithium hexafluorophosphate, and more preferably a composition of lithium perchlorate and lithium bis(oxalate)borate or lithium hexafluorophosphate.
[0016] In some specific implementations, the content of the lithium salt in the polymer electrolyte is 0.01wt% to 20wt%, preferably 0.1wt% to 15wt%, more preferably 0.5wt% to 13wt%, and most preferably 1wt% to 10wt%. Within the above content range, the combination of the lithium salt and the plastic crystal increases the number of defects in the plastic crystal structure, further improving the role of the plastic crystal, such as improving battery safety and room temperature ionic conductivity.
[0017] The present application adds 1-azabicyclo[2.2.2]octane and its derivatives to polymers and electrolytes to obtain polymer electrolytes, which can inhibit the growth of lithium dendrites and improve electrochemical stability, thereby improving the safety performance of batteries. At the same time, the plastic crystals and cross-linked polymers can form a double-layer polymer cross-linked network structure, forming a dual ion migration channel, ensuring high room temperature ion conductivity.
[0018] The present application also provides a method for preparing the polymer electrolyte described in the above technical solution, comprising the following steps:
[0019] Mixing the polymerization monomer, initiator and cross-linking agent uniformly to obtain a monomer prepolymer solution;
[0020] The plastic crystal and the lithium salt are mixed uniformly in a solvent to obtain a plastic crystal electrolyte solution; the plastic crystal is selected from 1-azabicyclo[2.2.2]octane and its derivatives;
[0021] The monomer prepolymer solution and the plastic crystal electrolyte solution are uniformly mixed, polymerized and cross-linked under heating conditions to obtain a polymer electrolyte.
[0022] The polymerization monomers, initiators, cross-linking agents, plasticizers and lithium salts and their amounts are the same as those described above and will not be described in detail in this application.
[0023] The present application uniformly mixes the polymerizable monomer, initiator and cross-linking agent to obtain a monomer prepolymer solution; and uniformly mixes the plastic crystal and lithium salt in the solution to obtain a plastic crystal electrolyte. The present application has no particular restrictions on the mixing method, and any mixing method known to those skilled in the art, such as manual stirring or mechanical stirring, can be used. In some specific implementations, the mixing is performed under an inert atmosphere, and the inert gas is preferably argon.
[0024] In some specific implementations, the solvent includes but is not limited to ethylene carbonate, fluoroethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, butylene carbonate, methyl propyl carbonate, methyl formate, ethyl formate, propyl formate, butyl formate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, 8-valerolactone, tetrahydrofuran, 2-methyltetrahydrofuran, 4-methyl 1,3-dioxolane, 2-methyl-1,3-dioxolane, ethylene glycol dimethyl ether, 1,3-dioxolane, cyclopentane and dimethyl sulfoxide, which can be one or more thereof. When the solvent is a composition of two or more, the application has no particular restrictions on the specific content of each substance. In some specific implementations, the solvent is preferably at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and 1,3-dioxolane.
[0025] After obtaining the monomer prepolymer solution and the plastic crystal electrolyte solution, mix them evenly, polymerize and crosslink under heating conditions to obtain a polymer electrolyte. The polymerized monomers are polymerized and crosslinked under the action of an initiator and a crosslinking agent to form a crosslinked network structure. The plastic crystal is filled in the crosslinked network structure formed by the crosslinked polymer. On the one hand, it is not easy to slide and enrich. On the other hand, a double-layer crosslinked network structure composed of a crosslinked polymer and a plastic crystal is constructed to form a dual ion channel, ensuring high room temperature ionic conductivity. The present application uses 1-azabicyclo[2.2.2]octane and its derivatives as plastic crystals, which can effectively inhibit the formation of lithium dendrites and improve the safety performance of the battery. In some specific implementations, the heating temperature is 30°C to 120°C, preferably 50°C to 80°C; the heating time is 2h to 72h, preferably 8h to 24h.
[0026] In some specific implementations, the mixed solution of the monomer prepolymer solution and the plastic crystal electrolyte solution includes:
[0027] 1 wt% to 90 wt% of a polymerizable monomer;
[0028] 0.01 wt% to 10 wt% of an initiator;
[0029] 1 wt% to 90 wt% of a cross-linking agent;
[0030] 0.01wt% to 50wt% plastic crystal;
[0031] 0.01wt% to 20wt% of lithium salt,
[0032] 0 to 60 wt% solvent.
[0033] In some specific implementations, the mixed solution of the monomer prepolymer solution and the plastic crystal electrolyte solution includes:
[0034] 5wt% to 70wt% of polymerization monomers;
[0035] 0.05 wt% to 8 wt% of an initiator;
[0036] 1 wt% to 60 wt% of a cross-linking agent;
[0037] 1wt% to 40wt% of plastic crystal;
[0038] 0.05wt% to 15wt% lithium salt,
[0039] 1 wt% to 50 wt% of solvent.
[0040] In some specific implementations, the mixed solution of the monomer prepolymer solution and the plastic crystal electrolyte solution includes:
[0041] 10 wt% to 50 wt% of a polymerizable monomer;
[0042] 0.1 wt% to 7 wt% of an initiator;
[0043] 1 wt% to 50 wt% of a cross-linking agent;
[0044] 3wt% to 40wt% plastic crystal;
[0045] 0.1wt% to 12wt% lithium salt,
[0046] 10 wt% to 40 wt% of solvent.
[0047] In some specific implementations, the mixed solution of the monomer prepolymer solution and the plastic crystal electrolyte solution includes:
[0048] 18 wt% to 24 wt% of polymerizable monomers;
[0049] 0.1 wt% to 1.0 wt% of an initiator;
[0050] 1 wt% to 3 wt% of a cross-linking agent;
[0051] 23wt% to 32wt% plastic crystal;
[0052] 5wt% to 12wt% lithium salt,
[0053] 35 wt% to 40 wt% solvent.
[0054] In fact, when the above polymer electrolyte is applied to a solid-state battery, the present application preferably generates the polymer electrolyte in situ inside the battery, that is, generates the polymer electrolyte by in-situ cross-linking polymerization. In-situ polymerization is a method of filling a polymer monomer between the positive and negative electrodes and using thermally initiated polymerization to form a polymer solid-state battery. This in-situ polymerization is believed to effectively reduce the interface impedance between the polymer electrolyte and the electrode.
[0055] Based on this, the present application provides a polymer solid-state battery, including a positive electrode, a negative electrode, a separator and an in-situ generated polymer electrolyte, wherein the polymer electrolyte includes 1wt% to 90wt% of a cross-linked polymer, 0.01wt% to 50wt% of a plastic crystal and 0.01wt% to 20wt% of a lithium salt; the plastic crystal is selected from 1-azabicyclo[2.2.2]octane and its derivatives.
[0056] The polymer solid-state battery provided in the present application includes a positive electrode. In some specific implementations, the positive electrode includes a positive electrode current collector and a positive electrode active material layer coated on the positive electrode current collector. In some specific implementations, the positive electrode current collector can be a metal foil, including but not limited to aluminum foil, nickel foil, stainless steel, etc. For example, the positive electrode current collector can be aluminum foil. The surface of the positive electrode current collector is coated with a positive electrode active material layer, which includes a positive electrode material, an optional conductive agent and an optional binder. In some specific implementations, the mass ratio of the positive electrode material, the conductive agent and the binder is 90-98:0.1-5:1-5, preferably 92-95:0.5-4:1.5-2. In some specific implementations, the positive electrode material includes but is not limited to LiFePO4 (LFP), LiCoO2 (LCO), LiNi x Co y Mn 1-x-y O2(NCM), LiMn2O4(LMO), LiMn x Fe 1-x PO4 (LMFP), etc., may be one or more thereof. When the positive electrode material is a mixture of multiple specific substances, the present application does not make too many restrictions on the ratio between the specific substances. In some specific implementations, the conductive agent includes but is not limited to carbon black, hard carbon, graphite, carbon nanotubes, graphene, silver powder, nickel powder, tin oxide, conductive titanium dioxide, etc., may be one or more thereof. When the conductive agent is a mixture of multiple specific substances, the present application does not make too many restrictions on the ratio between each specific substance. The binder includes but is not limited to polyvinylidene fluoride, polytetrafluoroethylene, polyacrylic acid, polyamide, lithium polyacrylate, methacrylate, sodium polymethylcellulose, aluminum dihydrogen phosphate, etc., may be one or more thereof. When the binder is a mixture of multiple specific substances, the present application does not make too many restrictions on the ratio between each specific substance.
[0057] The present application has no special restrictions on the preparation method of the positive electrode. The positive electrode material, the optional conductive agent and the optional binder are uniformly mixed in a solvent, such as N-methylpyrrolidone (NMP), coated on the positive electrode current collector in an optional manner, and dried to obtain a positive electrode sheet. Furthermore, after drying, rolling, die cutting, lamination, packaging, etc. are also included, and the present application has no special restrictions on them.
[0058] The solid-state battery includes a negative electrode, and the negative electrode includes a negative electrode current collector and a negative electrode active material layer coated on the negative electrode current collector. In some specific implementations, the negative electrode current collector may be a metal foil, including but not limited to aluminum foil, nickel foil, stainless steel, etc. For example, the negative electrode current collector may be an aluminum foil. The surface of the negative electrode current collector is coated with a negative electrode active material layer, which includes a negative electrode material, an optional conductive agent, an optional binder, and an optional thickener. In some specific implementations, the mass ratio of the negative electrode material, the conductive agent, the binder, and the thickener is 90 to 98: 0.5 to 2: 0.5 to 3: 1 to 5, preferably 92 to 97: 0.7 to 1.5: 0.8 to 2: 1 to 2. In some specific implementations, the negative electrode material includes but is not limited to graphite, hard carbon, soft carbon, lithium titanate, silicon-based composite materials, tin-based composite materials, and may be one or more thereof. When the negative electrode material is a mixture of multiple specific substances, the present application does not make too many restrictions on the ratio between the specific substances. In some specific implementations, the conductive agent includes but is not limited to carbon black, hard carbon, graphite, carbon nanotubes, graphene, silver powder, nickel powder, tin oxide, conductive titanium dioxide, etc., which can be one or more thereof, and when the conductive agent is a mixture of multiple specific substances, the application does not make too many restrictions on the ratio between each specific substance. The binder includes but is not limited to styrene-butadiene rubber (SBR), polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC-Na), polyacrylic acid (PAA), polytetrafluoroethylene (PTFE), polyimide (PI), etc., which can be one or more thereof, and when the binder is a mixture of multiple specific substances, the application does not make too many restrictions on the ratio between each specific substance. The thickener includes but is not limited to sodium carboxymethyl cellulose (CMC), polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), polytetrafluoroethylene (PTFE), polyimide (PI), etc., which can be one or more thereof, and when the thickener is a mixture of multiple specific substances, the application does not make too many restrictions on the ratio between each specific substance.
[0059] The present application has no special restrictions on the preparation method of the negative electrode, and the negative electrode material, the optional conductive agent, the optional binder and the optional thickener are uniformly mixed in a solvent, such as deionized water, and coated on the negative electrode current collector in an optional manner, and the negative electrode can be obtained after drying. Furthermore, after drying, rolling, die cutting, lamination, packaging, etc. are also included, and the present application has no special restrictions on them.
[0060] In some specific implementations, the diaphragm includes but is not limited to glass fiber microporous membrane, polyester microporous membrane, polyethylene microporous membrane, polypropylene microporous membrane, polytetrafluoroethylene microporous, ceramic coated diaphragm, etc.
[0061] The solid-state battery provided in the present application further includes a packaging film, which is used to contain the positive electrode, the negative electrode and the solid electrolyte. The present application has no special restrictions on the packaging film, which can be a packaging film well known to those skilled in the art, such as an aluminum-plastic film.
[0062] The solid-state battery provided in the present application also includes an in-situ generated polymer electrolyte, which is in-situ generated on the surface of the negative electrode, the separator and the positive electrode. The polymer electrolyte is as described above, and the present application will not repeat it here.
[0063] The present application also provides a method for preparing a solid-state battery, comprising the following steps:
[0064] Mixing the polymerization monomer, initiator and cross-linking agent uniformly to obtain a monomer prepolymer solution;
[0065] The plastic crystal and the lithium salt are mixed uniformly in a solvent to obtain a plastic crystal electrolyte solution; the plastic crystal is selected from 1-azabicyclo[2.2.2]octane and its derivatives;
[0066] The monomer prepolymer solution and the plastic crystal electrolyte solution are mixed evenly and then added into a battery consisting of a positive electrode, a negative electrode and a separator to form a polymer electrolyte in situ by polymerization and cross-linking.
[0067] The present application first prepares a monomer prepolymer solution and a plastic crystal electrolyte solution, with the same process and parameters as described above, and the present application has no special restrictions on this.
[0068] After obtaining the monomer prepolymer solution and the plastic crystal electrolyte solution, they are added to a battery composed of a positive electrode, a negative electrode and a separator, and polymerized and cross-linked to form a polymer electrolyte in situ. Specifically, the present application assembles the positive electrode, the negative electrode and the separator into a battery, and then adds the monomer prepolymer solution and the plastic crystal electrolyte solution, and obtains a solid polymer battery through the processes of packaging, infiltration, formation, aging, secondary vacuum packaging, and capacity division.
[0069] The present application has no special restrictions on the battery assembled by the positive electrode, the negative electrode and the separator. The positive electrode, the negative electrode and the separator are as described above, and the present application will not repeat them here. In some specific implementations, after the positive electrode, the separator and the negative electrode are stacked to form a bare battery cell, it is placed in a packaging film to form a battery with a cavity, and then the monomer prepolymer solution and the plastic crystal electrolyte solution are added to the battery, and a solid polymer battery is obtained through packaging, infiltration, polymerization curing, formation, aging, secondary vacuum packaging, and capacity division.
[0070] The present application has no special restrictions on the specific operations of the encapsulation, infiltration, polymerization curing, formation, aging, secondary vacuum packaging, and volume separation processes. Specifically, the parameters of the infiltration can be changed so that the monomer prepolymer solution and the plastic crystal electrolyte solution can fully infiltrate the positive electrode, the negative electrode, and the separator under the condition that the battery is static, thereby forming a uniformly distributed polymer electrolyte inside the battery. In some specific implementations, the infiltration temperature is room temperature and the time is 2h to 48h, preferably 6h to 10h.
[0071] After the impregnation is completed, polymerization curing is performed. The polymerization curing process is performed under heating conditions. Heating causes the polymer monomers to undergo in-situ crosslinking polymerization under the action of the initiator and the crosslinking agent to form a polymer electrolyte inside the battery. In some specific implementations, the heating temperature is 30°C to 120°C, preferably 50°C to 80°C; the heating time is 2h to 72h, preferably 8h to 24h.
[0072] The present application introduces 1-azabicyclo[2.2.2]octane and its derivatives into the polymer electrolyte. Compared with other plastic crystals, 1-azabicyclo[2.2.2]octane and its derivatives as additives can inhibit the growth of dendrites, improve electrochemical stability, and improve the safety performance of polymer solid-state batteries. At the same time, the present application adopts an in-situ cross-linking polymerization method to form a double-layer cross-linked network structure with plastic crystals and cross-linked polymers, thereby realizing rapid coordinated transport of lithium ions, thereby improving the room temperature ionic conductivity of the polymer solid-state battery and reducing its interface impedance. The experimental results show that the battery cycle retention rate, 3C rate discharge performance and safety performance prepared by the composite plastic crystal polymer solid electrolyte of the present invention are much higher than those of the polymer solid-state battery prepared without adding plastic crystals, and are also much higher than those of the polymer solid-state battery prepared with N,N-diethylpyrrolidone bistrifluorosulfonyl imide as the plastic crystal. DETAILED DESCRIPTION
[0073] The present invention provides a polymer electrolyte, a preparation method thereof and its application. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0074] The terms "include", "comprising" and "having" are used interchangeably herein and are intended to indicate the inclusiveness of the solution, meaning that the solution may have other elements in addition to the listed elements. At the same time, it should be understood that the use of "include", "comprising" and "having" descriptions herein also provides a "consisting of..." solution.
[0075] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B may represent: A exists alone, A and B exist at the same time, and B exists alone. A and B may be singular or plural.
[0076] In this application, "at least one" means one or more, "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items.
[0077] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the following processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0078] The present application provides a polymer electrolyte, comprising 1wt% to 90wt% of a cross-linked polymer, 0.01wt% to 50wt% of a plastic crystal and 0.01wt% to 20wt% of a lithium salt; the plastic crystal is selected from 1-azabicyclo[2.2.2]octane and its derivatives.
[0079] The present application uses 1-azabicyclo[2.2.2]octane and its derivatives as additives added to the polymer electrolyte. On the one hand, it can be homogenized with the polymer, thereby inhibiting the growth of dendrites and greatly improving the safety performance of the polymer solid-state battery. On the other hand, it can reduce the side reactions between the active substance and the electrode, improve the short-circuit resistance of the battery, and further improve the safety performance of the battery. In addition, the defects in the structure of 1-azabicyclo[2.2.2]octane and its derivatives can improve the rate of lithium ion migration at the interface. The rich electron groups in the polymer chain can have a strong complexation with lithium ions, promoting the dissociation of lithium salts to produce more free Li + , thereby effectively improving Li + Migration rate in the battery; the quaternary ammonium cation main chain of 1-azabicyclo[2.2.2]octane and its derivatives is positively charged, which can produce ion-dipole interaction force with the polymer chain segment, thereby inhibiting the movement of the polymer chain segment and improving the electrochemical stability of the polymer solid electrolyte; 1-azabicyclo[2.2.2]octane and its derivatives can produce conjugation with the end of the polymer precursor chain segment, control the reaction rate of polymer polymerization, reduce the crystallinity of the polymer, further adjust the lithium ion transport performance and mechanical properties of the solid polymer electrolyte, and construct a good positive electrode-electrolyte interface and a negative electrode-electrolyte interface, reduce the interface impedance between the two, and achieve a long cycle of the full battery.
[0080] The polymer electrolyte, preparation method and application thereof provided in the present application are further described below in conjunction with embodiments.
[0081] In the following examples, 1-azabicyclo[2.2.2]octane perchloric acid was synthesized according to the following method:
[0082]
[0083] Dissolve 1-azabicyclo[2.2.2]octane (1.0 g, 8.8 mmol) in a 50 mL round-bottom flask, slowly add an equimolar amount of perchloric acid aqueous solution (3.82 g, 8.8 mmol) dropwise under ice bath conditions, and react with stirring at room temperature for 24 h. After the reaction is completed, recrystallize several times to remove impurities, and slowly evaporate to obtain 1-azabicyclo[2.2.2]octane perchloric acid.
[0084] 1-Azabicyclo[2.2.2]octane-3-ol perchloric acid was synthesized as follows:
[0085]
[0086] The racemic 1-azabicyclo[2.2.2]octane-3-ol (1.0 g, 7.8 mmol) was dissolved in a round-bottom flask, and an equimolar amount of perchloric acid aqueous solution (2.33 g, 7.8 mmol) was slowly added dropwise under ice bath conditions, and the reaction was stirred at room temperature for 24 h. After the reaction was completed, the mixture was recrystallized several times to remove impurities, and the mixture was slowly evaporated to obtain 1-azabicyclo[2.2.2]octane-3-ol perchloric acid. Similarly, (S)-(+)-1-azabicyclo[2.2.2]octane-3-ol perchloric acid or (R)-(-)-1-azabicyclo[2.2.2]octane-3-ol perchloric acid was prepared using left-handed 1-azabicyclo[2.2.2]octane-3-ol or right-handed 1-azabicyclo[2.2.2]octane-3-ol as raw materials.
[0087] Example 1
[0088] (1) 1.60 g of ethoxylated trimethylolpropane triacrylate, 0.15 g of azobisisobutyronitrile and 0.55 g of trimethylolpropane propoxylate triacrylate were mixed uniformly in a glove box filled with argon to obtain a flowing monomer prepolymer solution;
[0089] 1.00 g of 1-azabicyclo[2.2.2]octane perchloric acid, 0.15 g of lithium perchlorate, and 0.05 g of lithium hexafluorophosphate were uniformly mixed in 1.50 g of ethylene carbonate to obtain a plastic crystal electrolyte solution;
[0090] (2) Lithium iron phosphate (LiFePO4), conductive carbon black (Super-P) and binder polyvinylidene fluoride (PVDF) were mixed and ball-milled in a ratio of 96:2:2 for 20 hours, with N-methylpyrrolidone (NMP) as the solvent and a solid-liquid ratio of 45%. The obtained slurry was coated on the surface of aluminum foil, dried with air at 110°C for 8 hours, and a 12 mm positive electrode disc was obtained by cutting; the positive electrode disc, polyethylene separator, and lithium sheet negative electrode were assembled into the first half cell according to the structure of positive electrode||separator||negative electrode for charge and discharge test; the steel sheet positive electrode, polyethylene separator, and steel sheet negative electrode were assembled into a battery with blocking electrodes on both sides according to the structure of steel sheet||separator||steel sheet for ion conductivity test.
[0091] After the monomer prepolymer solution obtained in step (1) is evenly mixed with the plastic crystal electrolyte solution, it is injected into the first half-cell and the second half-cell respectively for infiltration, and the positive electrode layer, the negative electrode layer and the separator layer are fully infiltrated; after standing at room temperature for 8 hours, it is cured at 80°C for 24 hours to solidify the mixed solution in situ inside the half-cell to form a composite plastic crystal polymer solid electrolyte.
[0092] (3) lithium iron phosphate (LiFePO4), conductive agent carbon black (Super-P), and binder polyvinylidene fluoride (PVDF) are weighed and mixed in a mass ratio of 97.8:0.7:1.5 to form a uniform positive electrode active material slurry, and the positive electrode active material slurry is coated on the surface of the positive electrode current collector aluminum foil, and after drying, cold pressing, and die cutting, a positive electrode sheet is obtained;
[0093] The negative electrode material artificial graphite, the conductive agent carbon black (Super-P), the thickener sodium carboxymethyl cellulose (CMC), and the binder styrene butadiene rubber (SBR) are mixed in a mass ratio of 96.5:0.5:1.2:1.8 to form a uniform negative electrode active material slurry; the negative electrode active material slurry is coated on the surface of the negative electrode current collector copper foil, and after drying, cold pressing, and die cutting, a negative electrode active material layer is formed on the surface of the copper foil to obtain a negative electrode sheet;
[0094] A soft-pack laminated battery is prepared by using a ceramic isolation membrane as a diaphragm at an ambient dew point of ≤-45°C, stacking the positive electrode sheet, the diaphragm and the negative electrode sheet in order, with the positive and negative electrode tabs on the same side, so that the diaphragm is located between the positive and negative electrode sheets to play an isolating role, and obtaining a bare battery cell; the bare battery cell is placed in an aluminum-plastic film outer package, vacuum-baked at 90°C for 12 hours, and then injected with a mixture of the monomer prepolymer solution and the plastic crystal electrolyte solution obtained in step (1), followed by packaging, soaking at room temperature for 8 hours, curing at 80°C for 24 hours, formation, aging, secondary vacuum packaging, and capacity division to obtain a battery for safety performance testing.
[0095] Example 2
[0096] (1) 1.50 g of vinyl acetate, 0.02 g of methyl ethyl ketone peroxide, and 0.50 g of polyethylene glycol methacrylate were mixed uniformly in a glove box filled with argon gas to obtain a flowing monomer prepolymer solution;
[0097] 1.15 g of 1-azabicyclo[2.2.2]octane perchloric acid, 0.13 g of lithium perchlorate, and 0.05 g of lithium bis(oxalatoborate) were uniformly mixed in 1.66 g of propylene carbonate to obtain a plastic crystal electrolyte solution;
[0098] (2) Lithium cobalt oxide (LiCoO2), conductive carbon black (Super-P) and binder polyvinylidene fluoride (PVDF) were mixed and ball-milled in a ratio of 96:2:2 for 20 hours, with NMP as the solvent and a solid-liquid ratio of 45%. The obtained slurry was coated on the surface of aluminum foil, dried with air at 110°C for 8 hours, and a 12 mm positive electrode disc was obtained by cutting; the positive electrode disc, polyethylene separator, and lithium sheet negative electrode were assembled into the first half cell according to the structure of positive electrode||separator||negative electrode for charge and discharge test; the steel sheet positive electrode, polyethylene separator, and steel sheet negative electrode were assembled into a battery with blocking electrodes on both sides according to the structure of steel sheet||separator||steel sheet for ion conductivity test.
[0099] After the monomer prepolymer solution obtained in step (1) is evenly mixed with the plastic crystal electrolyte solution, it is injected into the first half-cell and the second half-cell respectively for infiltration, and the positive electrode layer, the negative electrode layer and the separator layer are fully infiltrated; after standing at room temperature for 7 hours, it is cured at 75°C for 24 hours to solidify the mixed solution in situ inside the battery to form a composite plastic crystal polymer solid electrolyte.
[0100] (3) lithium cobalt oxide (LiCoO2), conductive agent carbon black (Super-P), binder polyvinylidene fluoride (PVDF), and conductive agent carbon nanotube (CNT) are weighed and mixed according to a mass ratio of 97.0:1.2:0.8:1 to form a uniform positive electrode active material slurry, and the positive electrode active material slurry is coated on the surface of the positive electrode current collector aluminum foil, and after drying, cold pressing, and die cutting, a positive electrode sheet is obtained;
[0101] The negative electrode material artificial graphite, the conductive agent carbon black (Super-P), the thickener sodium carboxymethyl cellulose (CMC), and the binder styrene-butadiene rubber (SBR) are mixed in a mass ratio of 96.5:1:1.2:1.3 to form a uniform negative electrode active material slurry; the negative electrode active material slurry is coated on the surface of the negative electrode current collector copper foil, and after drying, cold pressing, and die cutting, a negative electrode active material layer is formed on the surface of the copper foil to obtain a negative electrode sheet;
[0102] A soft-pack laminated battery is prepared at an ambient dew point of ≤-45°C using a ceramic separator as a separator. The positive electrode, separator, and negative electrode are stacked in order, with the positive and negative electrode tabs on the same side, so that the separator is located between the positive and negative electrode sheets to play an isolating role, and a bare cell is obtained. The bare cell is placed in an aluminum-plastic film outer package, vacuum-baked at 90°C for 12 hours, cooled to below 40°C, and then injected with a mixture of the monomer prepolymer solution and the plastic crystal electrolyte solution obtained in step (1), followed by packaging, room temperature infiltration for 7 hours, 75°C curing for 24 hours, formation, aging, secondary vacuum packaging, and capacity division to obtain a battery for safety performance testing.
[0103] Example 3
[0104] (1) 1.55 g of ethoxylated trimethylolpropane triacrylate, 0.16 g of azobisisobutyronitrile and 0.60 g of trimethylolpropane propoxylate triacrylate were mixed uniformly in a glove box filled with argon to obtain a flowing monomer prepolymer solution;
[0105] 1.10 g of (R)-(-)-1-azabicyclo[2.2.2]octan-3-ol perchloric acid, 0.14 g of lithium perchlorate, and 0.06 g of lithium hexafluorophosphate were uniformly mixed in 1.39 g of diethyl carbonate to obtain a plastic crystal electrolyte solution;
[0106] (2) Lithium iron phosphate (LiFePO4), conductive carbon black (Super-P) and binder polyvinylidene fluoride (PVDF) were mixed and ball-milled in a ratio of 96:2:2 for 20 hours, with NMP as the solvent and a solid-liquid ratio of 45%. The obtained slurry was coated on the surface of aluminum foil, dried with air at 110°C for 8 hours, and a 12 mm positive electrode disc was obtained by cutting; the positive electrode disc, polyethylene separator, and lithium sheet negative electrode were assembled into the first half cell according to the structure of positive electrode||separator||negative electrode for charge and discharge test; the steel sheet positive electrode, polyethylene separator, and steel sheet negative electrode were assembled into a battery with blocking electrodes on both sides according to the structure of steel sheet||separator||steel sheet for ion conductivity test.
[0107] After the monomer prepolymer solution obtained in step (1) is evenly mixed with the plastic crystal electrolyte solution, it is injected into the first half-cell and the second half-cell respectively for infiltration, and the positive electrode layer, the negative electrode layer and the separator layer are fully infiltrated; after standing at room temperature for 8 hours, it is cured at 80°C for 24 hours to solidify the mixed solution in situ inside the battery to form a composite plastic crystal polymer solid electrolyte.
[0108] (3) lithium iron phosphate (LiFePO4), conductive carbon black (Super-P) and binder polyvinylidene fluoride (PVDF) are weighed and mixed in a mass ratio of 97.8:0.7:1.5 to form a uniform positive electrode active material slurry, and the positive electrode active material slurry is coated on the surface of the positive electrode current collector aluminum foil, and after drying, cold pressing and die cutting, a positive electrode sheet is obtained;
[0109] The negative electrode material artificial graphite, conductive carbon black (Super-P), thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) are mixed in a mass ratio of 96.5:0.5:1.2:1.8 to form a uniform negative electrode active material slurry; the negative electrode active material slurry is coated on the surface of the negative electrode current collector copper foil, and after drying, cold pressing, and die cutting, a negative electrode active material layer is formed on the surface of the copper foil to obtain a negative electrode sheet;
[0110] Using ceramic separator as separator, soft-pack laminated battery is made at an ambient dew point of ≤-45℃. The positive electrode, separator and negative electrode are stacked in order, with the positive and negative electrode tabs on the same side, so that the separator is in the middle of the positive and negative electrode sheets to play an isolating role, and a bare cell is obtained. The bare cell is placed in an aluminum-plastic film outer package, vacuum-baked at 90℃ for 12h, and then injected with the prepared electrolyte after cooling to below 40℃, followed by packaging, room temperature infiltration for 8h, 80℃ curing for 24h, formation, aging, secondary vacuum packaging, and capacity division to obtain a battery for safety performance testing.
[0111] Example 4
[0112] (1) 1.65 g of vinyl acetate, 0.15 g of methyl ethyl ketone peroxide, and 0.55 g of polyethylene glycol methacrylate were mixed uniformly in a glove box filled with argon gas to obtain a flowing monomer prepolymer solution;
[0113] 1.05 g of (R)-(-)-1-azabicyclo[2.2.2]octan-3-ol perchloric acid, 0.15 g of lithium perchlorate, and 0.06 g of lithium bis(oxalatoborate) were uniformly mixed in 1.41 g of propylene carbonate to obtain a plastic crystal electrolyte solution;
[0114] (2) Lithium cobalt oxide (LiCoO2), conductive carbon black (Super-P) and binder polyvinylidene fluoride (PVDF) were mixed and ball-milled in a ratio of 96:2:2 for 20 hours, with NMP as the solvent and a solid-liquid ratio of 45%. The obtained slurry was coated on the surface of aluminum foil, dried with air at 110°C for 8 hours, and a 12 mm positive electrode disc was obtained by cutting; the positive electrode disc, polyethylene separator, and lithium sheet negative electrode were assembled into the first half cell according to the structure of positive electrode||separator||negative electrode for charge and discharge test; the steel sheet positive electrode, polyethylene separator, and steel sheet negative electrode were assembled into a battery with blocking electrodes on both sides according to the structure of steel sheet||separator||steel sheet for ion conductivity test.
[0115] After the monomer prepolymer solution obtained in step (1) is evenly mixed with the plastic crystal electrolyte solution, it is injected into the first half-cell and the second half-cell respectively for infiltration, and the positive electrode layer, the negative electrode layer and the separator layer are fully infiltrated; after standing at room temperature for 7 hours, it is cured at 75°C for 24 hours to solidify the mixed solution in situ inside the battery to form a composite plastic crystal polymer solid electrolyte.
[0116] (3) lithium cobalt oxide (LiCoO2), conductive carbon black (Super-P), binder polyvinylidene fluoride (PVDF) and conductive agent carbon nanotube (CNT) are weighed and mixed in a mass ratio of 97.0:1.2:0.8:1 to form a uniform positive electrode active material slurry, and the positive electrode active material slurry is coated on the surface of the positive electrode current collector aluminum foil, and after drying, cold pressing and die cutting, a positive electrode sheet is obtained;
[0117] The negative electrode material artificial graphite, conductive carbon black (Super-P), thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) are mixed in a mass ratio of 96.5:1:1.2:1.3 to form a uniform negative electrode active material slurry; the negative electrode active material slurry is coated on the surface of the negative electrode current collector copper foil, and after drying, cold pressing, and die cutting, a negative electrode active material layer is formed on the surface of the copper foil to obtain a negative electrode sheet;
[0118] A soft-pack laminated battery is prepared at an ambient dew point of ≤-45°C using a ceramic separator as a separator. The positive electrode, separator, and negative electrode are stacked in order, with the positive and negative electrode tabs on the same side, so that the separator is located between the positive and negative electrode sheets to play an isolating role, and a bare cell is obtained. The bare cell is placed in an aluminum-plastic film outer package, vacuum-baked at 90°C for 12 hours, cooled to below 40°C, and then injected with a mixture of the monomer prepolymer solution and the plastic crystal electrolyte solution obtained in step (1), followed by packaging, room temperature infiltration for 7 hours, 75°C curing for 24 hours, formation, aging, secondary vacuum packaging, and capacity division to obtain a battery for safety performance testing.
[0119] Example 5
[0120] (1) 1.57 g of ethoxylated trimethylolpropane triacrylate, 0.14 g of azobisisobutyronitrile and 0.56 g of trimethylolpropane propoxylate triacrylate were mixed uniformly in a glove box filled with argon to obtain a flowing monomer prepolymer solution;
[0121] 1.11 g of (S)-(+)-1-azabicyclo[2.2.2]octan-3-ol perchloric acid, 0.16 g of lithium perchlorate, and 0.05 g of lithium hexafluorophosphate were uniformly mixed in 1.42 g of diethyl carbonate to obtain a plastic crystal electrolyte solution;
[0122] (2) Lithium iron phosphate (LiFePO4), conductive carbon black (Super-P) and binder polyvinylidene fluoride (PVDF) were mixed and ball-milled in a ratio of 96:2:2 for 20 hours, with NMP as the solvent and a solid-liquid ratio of 45%. The obtained slurry was coated on the surface of aluminum foil, dried with air at 110°C for 8 hours, and a 12 mm positive electrode disc was obtained by cutting; the positive electrode disc, polyethylene separator, and lithium sheet negative electrode were assembled into the first half cell according to the structure of positive electrode||separator||negative electrode for charge and discharge test; the steel sheet positive electrode, polyethylene separator, and steel sheet negative electrode were assembled into a battery with blocking electrodes on both sides according to the structure of steel sheet||separator||steel sheet for ion conductivity test.
[0123] After the monomer prepolymer solution obtained in step (1) is evenly mixed with the plastic crystal electrolyte solution, it is injected into the first half-cell and the second half-cell respectively for infiltration, and the positive electrode layer, the negative electrode layer and the separator layer are fully infiltrated; after standing at room temperature for 8 hours, it is cured at 80°C for 24 hours to solidify the mixed solution in situ inside the battery to form a composite plastic crystal polymer solid electrolyte.
[0124] (3) lithium iron phosphate (LiFePO4), conductive carbon black (Super-P) and binder polyvinylidene fluoride (PVDF) are weighed and mixed in a mass ratio of 97.8:0.7:1.5 to form a uniform positive electrode active material slurry, and the positive electrode active material slurry is coated on the surface of the positive electrode current collector aluminum foil, and after drying, cold pressing and die cutting, a positive electrode sheet is obtained;
[0125] The negative electrode material artificial graphite, conductive carbon black (Super-P), thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) are mixed in a mass ratio of 96.5:0.5:1.2:1.8 to form a uniform negative electrode active material slurry; the negative electrode active material slurry is coated on the surface of the negative electrode current collector copper foil, and after drying, cold pressing, and die cutting, a negative electrode active material layer is formed on the surface of the copper foil to obtain a negative electrode sheet;
[0126] A soft-pack laminated battery is prepared at an ambient dew point of ≤-45°C using a ceramic separator as a separator. The positive electrode, separator, and negative electrode are stacked in order, with the positive and negative electrode tabs on the same side, so that the separator is located between the positive and negative electrode sheets to play an isolating role, and a bare cell is obtained. The bare cell is placed in an aluminum-plastic film outer package, vacuum-baked at 90°C for 12 hours, cooled to below 40°C, and then injected with a mixture of the monomer prepolymer solution and the plastic crystal electrolyte solution obtained in step (1), followed by packaging, room temperature infiltration for 8 hours, 80°C curing for 24 hours, formation, aging, secondary vacuum packaging, and capacity division to obtain a battery for safety performance testing.
[0127] Example 6
[0128] (1) 1.59 g of vinyl acetate, 0.16 g of methyl ethyl ketone peroxide, and 0.54 g of polyethylene glycol methacrylate were mixed uniformly in a glove box filled with argon gas to obtain a flowing monomer prepolymer solution;
[0129] 1.07 g of (S)-(+)-1-azabicyclo[2.2.2]octan-3-ol perchloric acid, 0.16 g of lithium perchlorate, and 0.06 g of lithium dioxalatoborate were uniformly mixed in 1.44 g of propylene carbonate to obtain a plastic crystal electrolyte solution;
[0130] (2) Lithium cobalt oxide (LiCoO2), conductive carbon black (Super-P) and binder polyvinylidene fluoride (PVDF) were mixed and ball-milled in a ratio of 96:2:2 for 20 hours, with NMP as the solvent and a solid-liquid ratio of 45%. The obtained slurry was coated on the surface of aluminum foil, dried with air at 110°C for 8 hours, and a 12 mm positive electrode disc was obtained by cutting; the positive electrode disc, polyethylene separator, and lithium sheet negative electrode were assembled into the first half cell according to the structure of positive electrode||separator||negative electrode for charge and discharge test; the steel sheet positive electrode, polyethylene separator, and steel sheet negative electrode were assembled into a battery with blocking electrodes on both sides according to the structure of steel sheet||separator||steel sheet for ion conductivity test.
[0131] After the monomer prepolymer solution obtained in step (1) is evenly mixed with the plastic crystal electrolyte solution, it is injected into the first half-cell and the second half-cell respectively for infiltration, and the positive electrode layer, the negative electrode layer and the separator layer are fully infiltrated; after standing at room temperature for 7 hours, it is cured at 75°C for 24 hours to solidify the mixed solution in situ inside the battery to form a composite plastic crystal polymer solid electrolyte.
[0132] (3) lithium cobalt oxide (LiCoO2), conductive carbon black (Super-P), binder polyvinylidene fluoride (PVDF), and conductive agent carbon nanotube (CNT) are weighed and mixed in a mass ratio of 97.0:1.2:0.8:1 to form a uniform positive electrode active material slurry, and the positive electrode active material slurry is coated on the surface of the positive electrode current collector aluminum foil, and after drying, cold pressing, and die cutting, a positive electrode sheet is obtained;
[0133] The negative electrode material artificial graphite, conductive carbon black (Super-P), thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) are mixed in a mass ratio of 96.5:1:1.2:1.3 to form a uniform negative electrode active material slurry; the negative electrode active material slurry is coated on the surface of the negative electrode current collector copper foil, and after drying, cold pressing, and die cutting, a negative electrode active material layer is formed on the surface of the copper foil to obtain a negative electrode sheet;
[0134] A soft-pack laminated battery is prepared at an ambient dew point of ≤-45°C using a ceramic separator as a separator. The positive electrode, separator, and negative electrode are stacked in order, with the positive and negative electrode tabs on the same side, so that the separator is located between the positive and negative electrode sheets to play an isolating role, and a bare cell is obtained. The bare cell is placed in an aluminum-plastic film outer package, vacuum-baked at 90°C for 12 hours, cooled to below 40°C, and then injected with a mixture of the monomer prepolymer solution and the plastic crystal electrolyte solution obtained in step (1), followed by packaging, room temperature infiltration for 7 hours, 75°C curing for 24 hours, formation, aging, secondary vacuum packaging, and capacity division to obtain a battery for safety performance testing.
[0135] Example 7
[0136] (1) 1.54 g of ethoxylated trimethylolpropane triacrylate, 0.15 g of azobisisobutyronitrile and 0.55 g of trimethylolpropane propoxylate triacrylate were mixed uniformly in a glove box filled with argon to obtain a flowing monomer prepolymer solution;
[0137] 1.10 g of 1-azabicyclo[2.2.2]octan-3-ol perchloric acid, 0.15 g of lithium perchlorate, and 0.06 g of lithium hexafluorophosphate were uniformly mixed in 1.46 g of diethyl carbonate to obtain a plastic crystal electrolyte solution;
[0138] (2) Lithium iron phosphate (LiFePO4), conductive carbon black (Super-P) and binder polyvinylidene fluoride (PVDF) were mixed and ball-milled in a ratio of 96:2:2 for 20 hours, with NMP as the solvent and a solid-liquid ratio of 45%. The obtained slurry was coated on the surface of aluminum foil, dried with air at 110°C for 8 hours, and a 12 mm positive electrode disc was obtained by cutting; the positive electrode disc, polyethylene separator, and lithium sheet negative electrode were assembled into the first half cell according to the structure of positive electrode||separator||negative electrode for charge and discharge test; the steel sheet positive electrode, polyethylene separator, and steel sheet negative electrode were assembled into a battery with blocking electrodes on both sides according to the structure of steel sheet||separator||steel sheet for ion conductivity test.
[0139] After the monomer prepolymer solution obtained in step (1) is evenly mixed with the plastic crystal electrolyte solution, it is injected into the first half-cell and the second half-cell respectively for infiltration, and the positive electrode layer, the negative electrode layer and the separator layer are fully infiltrated; after standing at room temperature for 8 hours, it is cured at 80°C for 24 hours to solidify the mixed solution in situ inside the battery to form a composite plastic crystal polymer solid electrolyte.
[0140] (3) lithium iron phosphate (LiFePO4), conductive carbon black (Super-P) and binder polyvinylidene fluoride (PVDF) are weighed and mixed in a mass ratio of 97.8:0.7:1.5 to form a uniform positive electrode active material slurry, and the positive electrode active material slurry is coated on the surface of the positive electrode current collector aluminum foil, and after drying, cold pressing and die cutting, a positive electrode sheet is obtained;
[0141] The negative electrode material artificial graphite, conductive carbon black (Super-P), thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) are mixed in a mass ratio of 96.5:0.5:1.2:1.8 to form a uniform negative electrode active material slurry; the negative electrode active material slurry is coated on the surface of the negative electrode current collector copper foil, and after drying, cold pressing, and die cutting, a negative electrode active material layer is formed on the surface of the copper foil to obtain a negative electrode sheet;
[0142] A soft-pack laminated battery is prepared at an ambient dew point of ≤-45°C using a ceramic separator as a separator. The positive electrode, separator, and negative electrode are stacked in order, with the positive and negative electrode tabs on the same side, so that the separator is located between the positive and negative electrode sheets to play an isolating role, and a bare cell is obtained. The bare cell is placed in an aluminum-plastic film outer package, vacuum-baked at 90°C for 12 hours, cooled to below 40°C, and then injected with a mixture of the monomer prepolymer solution and the plastic crystal electrolyte solution obtained in step (1), followed by packaging, room temperature infiltration for 8 hours, 80°C curing for 24 hours, formation, aging, secondary vacuum packaging, and capacity division to obtain a battery for safety performance testing.
[0143] Example 8
[0144] (1) 1.56 g of vinyl acetate, 0.13 g of methyl ethyl ketone peroxide, and 0.56 g of polyethylene glycol methacrylate were mixed uniformly in a glove box filled with argon gas to obtain a flowing monomer prepolymer solution;
[0145] 1.11 g of 1-azabicyclo[2.2.2]octane perchloric acid, 0.17 g of lithium perchlorate, and 0.05 g of lithium bis(oxalatoborate) were uniformly mixed in 1.44 g of propylene carbonate to obtain a plastic crystal electrolyte solution;
[0146] (2) Lithium cobalt oxide (LiCoO2), conductive carbon black (Super-P) and binder polyvinylidene fluoride (PVDF) were mixed and ball-milled in a ratio of 96:2:2 for 20 hours, with NMP as the solvent and a solid-liquid ratio of 45%. The obtained slurry was coated on the surface of aluminum foil, dried with air at 110°C for 8 hours, and a 12 mm positive electrode disc was obtained by cutting; the positive electrode disc, polyethylene separator, and lithium sheet negative electrode were assembled into the first half cell according to the structure of positive electrode||separator||negative electrode for charge and discharge test; the steel sheet positive electrode, polyethylene separator, and steel sheet negative electrode were assembled into a battery with blocking electrodes on both sides according to the structure of steel sheet||separator||steel sheet for ion conductivity test.
[0147] After the monomer prepolymer solution obtained in step (1) is evenly mixed with the plastic crystal electrolyte solution, it is injected into the first half-cell and the second half-cell respectively for infiltration, and the positive electrode layer, the negative electrode layer and the separator layer are fully infiltrated; after standing at room temperature for 7 hours, it is cured at 75°C for 24 hours to solidify the mixed solution in situ inside the battery to form a composite plastic crystal polymer solid electrolyte.
[0148] (3) lithium cobalt oxide (LiCoO2), conductive carbon black (Super-P), binder polyvinylidene fluoride (PVDF), and conductive agent carbon nanotube (CNT) are weighed and mixed in a mass ratio of 97.0:1.2:0.8:1 to form a uniform positive electrode active material slurry, and the positive electrode active material slurry is coated on the surface of the positive electrode current collector aluminum foil, and after drying, cold pressing, and die cutting, a positive electrode sheet is obtained;
[0149] The negative electrode material artificial graphite, conductive carbon black (Super-P), thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) are mixed in a mass ratio of 96.5:1:1.2:1.3 to form a uniform negative electrode active material slurry; the negative electrode active material slurry is coated on the surface of the negative electrode current collector copper foil, and after drying, cold pressing, and die cutting, a negative electrode active material layer is formed on the surface of the copper foil to obtain a negative electrode sheet;
[0150] A soft-pack laminated battery is prepared at an ambient dew point of ≤-45°C using a ceramic separator as a separator. The positive electrode, separator, and negative electrode are stacked in order, with the positive and negative electrode tabs on the same side, so that the separator is located between the positive and negative electrode sheets to play an isolating role, and a bare cell is obtained. The bare cell is placed in an aluminum-plastic film outer package, vacuum-baked at 90°C for 12 hours, cooled to below 40°C, and then injected with a mixture of the monomer prepolymer solution and the plastic crystal electrolyte solution obtained in step (1), followed by packaging, room temperature infiltration for 7 hours, 75°C curing for 24 hours, formation, aging, secondary vacuum packaging, and capacity division to obtain a battery for safety performance testing.
[0151] Comparative Example 1
[0152] (1) 1.60 g of ethoxylated trimethylolpropane triacrylate, 0.15 g of azobisisobutyronitrile and 0.55 g of trimethylolpropane propoxylate triacrylate were mixed uniformly in a glove box filled with argon to obtain a flowing monomer prepolymer solution;
[0153] 0.15 g of lithium perchlorate and 0.05 g of lithium hexafluorophosphate were uniformly mixed in 2.50 g of ethylene carbonate to obtain an electrolyte solution;
[0154] (2) Lithium iron phosphate (LiFePO4), conductive carbon black (Super-P) and binder polyvinylidene fluoride (PVDF) were mixed and ball-milled in a ratio of 96:2:2 for 20 hours. The solvent was NMP and the solid-liquid ratio was 45%. The obtained slurry was coated on the surface of aluminum foil and dried at 110°C for 8 hours. The surface density of the active material was controlled at 10 mg cm -2 . A 12 mm positive electrode disc was obtained by cutting; the positive electrode disc, polyethylene separator, and lithium negative electrode were assembled into a first half cell according to the structure of positive electrode||separator||negative electrode for charge and discharge test; the steel positive electrode, polyethylene separator, and steel negative electrode were assembled into a cell with blocking electrodes on both sides according to the structure of steel sheet||separator||steel sheet for ion conductivity test.
[0155] The monomer prepolymer solution obtained in step (1) is mixed evenly with the electrolyte solution, and then injected into the first half cell and the second half cell respectively for infiltration, so as to fully infiltrate the positive electrode layer, the negative electrode layer and the separator layer; after standing at room temperature for 8 hours, the mixture is cured at 80°C for 24 hours, so that the mixture is solidified in situ inside the battery to form a polymer solid electrolyte.
[0156] (3) lithium iron phosphate (LiFePO4), conductive carbon black (Super-P) and binder polyvinylidene fluoride (PVDF) are weighed and mixed in a mass ratio of 97.8:0.7:1.5 to form a uniform positive electrode active material slurry, and the positive electrode active material slurry is coated on the surface of the positive electrode current collector aluminum foil, and after drying, cold pressing and die cutting, a positive electrode sheet is obtained;
[0157] The negative electrode material artificial graphite, conductive carbon black (Super-P), thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) are mixed in a mass ratio of 96.5:0.5:1.2:1.8 to form a uniform negative electrode active material slurry; the negative electrode active material slurry is coated on the surface of the negative electrode current collector copper foil, and after drying, cold pressing, and die cutting, a negative electrode active material layer is formed on the surface of the copper foil to obtain a negative electrode sheet;
[0158] A soft-pack laminated battery is prepared at an ambient dew point of ≤-45°C using a ceramic separator as a separator, and the positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the positive and negative electrode tabs on the same side, so that the separator is located between the positive and negative electrode sheets to play an isolating role, and a bare cell is obtained. The bare cell is placed in an aluminum-plastic film outer package, vacuum-baked at 90°C for 12 hours, cooled to below 40°C, and then injected with a mixture of the monomer prepolymer solution and the electrolyte solution obtained in step (1), followed by packaging, room temperature infiltration for 8 hours, 80°C curing for 24 hours, formation, aging, secondary vacuum packaging, and capacity division to obtain a battery for safety performance testing.
[0159] Comparative Example 2
[0160] (1) 1.55 g of ethoxylated trimethylolpropane triacrylate, 0.16 g of azobisisobutyronitrile and 0.60 g of trimethylolpropane propoxylate triacrylate were mixed uniformly in a glove box filled with argon to obtain a flowing monomer prepolymer solution;
[0161] 0.14 g of lithium perchlorate and 0.06 g of lithium hexafluorophosphate were uniformly mixed in 2.49 g of diethyl carbonate to obtain an electrolyte solution;
[0162] (2) Lithium cobalt oxide (LiCoO2), conductive carbon black (Super-P) and binder polyvinylidene fluoride (PVDF) were mixed and ball-milled in a ratio of 96:2:2 for 20 hours, with NMP as the solvent and a solid-liquid ratio of 45%. The obtained slurry was coated on the surface of aluminum foil, dried with air at 110°C for 8 hours, and a 12 mm positive electrode disc was obtained by cutting; the positive electrode disc, polyethylene separator, and lithium sheet negative electrode were assembled into the first half cell according to the structure of positive electrode||separator||negative electrode for charge and discharge test; the steel sheet positive electrode, polyethylene separator, and steel sheet negative electrode were assembled into a battery with blocking electrodes on both sides according to the structure of steel sheet||separator||steel sheet for ion conductivity test.
[0163] The monomer prepolymer solution obtained in step (1) is mixed evenly with the electrolyte solution, and then injected into the first half-cell and the second half-cell respectively for infiltration, so as to fully infiltrate the positive electrode layer, the negative electrode layer and the separator layer; after standing at room temperature for 7 hours, the mixture is cured at 75°C for 24 hours, so that the mixture is solidified in situ inside the battery to form a polymer solid electrolyte.
[0164] (3) lithium cobalt oxide (LiCoO2), conductive carbon black (Super-P), binder polyvinylidene fluoride (PVDF) and conductive agent carbon nanotube (CNT) are weighed and mixed in a mass ratio of 97.0:1.2:0.8:1 to form a uniform positive electrode active material slurry, and the positive electrode active material slurry is coated on the surface of the positive electrode current collector aluminum foil, and after drying, cold pressing and die cutting, a positive electrode sheet is obtained;
[0165] The negative electrode material artificial graphite, conductive carbon black (Super-P), thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) are mixed in a mass ratio of 96.5:1:1.2:1.3 to form a uniform negative electrode active material slurry; the negative electrode active material slurry is coated on the surface of the negative electrode current collector copper foil, and after drying, cold pressing, and die cutting, a negative electrode active material layer is formed on the surface of the copper foil to obtain a negative electrode sheet;
[0166] A soft-pack laminated battery is prepared at an ambient dew point of ≤-45°C using a ceramic separator as a separator, and the positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the positive and negative electrode tabs on the same side, so that the separator is located between the positive and negative electrode sheets to play an isolating role, and a bare cell is obtained. The bare cell is placed in an aluminum-plastic film outer package, vacuum-baked at 90°C for 12 hours, cooled to below 40°C, and then injected with a mixture of the monomer prepolymer solution and the electrolyte solution obtained in step (1), followed by packaging, room temperature infiltration for 7 hours, 75°C curing for 24 hours, formation, aging, secondary vacuum packaging, and capacity division to obtain a battery for safety performance testing.
[0167] Comparative Example 3
[0168] (1) 1.59 g of vinyl acetate, 0.16 g of methyl ethyl ketone peroxide, and 0.54 g of polyethylene glycol methacrylate were mixed uniformly in a glove box filled with argon gas to obtain a flowing monomer prepolymer solution;
[0169] 0.16 g of lithium perchlorate and 0.06 g of lithium borate oxalate were uniformly mixed in 2.51 g of propylene carbonate to obtain an electrolyte solution;
[0170] (2) Lithium iron phosphate (LiFePO4), conductive carbon black (Super-P) and binder polyvinylidene fluoride (PVDF) were mixed and ball-milled in a ratio of 96:2:2 for 20 hours. The solvent was NMP and the solid-liquid ratio was 45%. The obtained slurry was coated on the surface of aluminum foil and dried at 110°C for 8 hours. The surface density of the active material was controlled at 10 mg cm -2 . A 12 mm positive electrode disc was obtained by cutting; the positive electrode disc, polyethylene separator, and lithium negative electrode were assembled into a first half cell according to the structure of positive electrode||separator||negative electrode for charge and discharge test; the steel positive electrode, polyethylene separator, and steel negative electrode were assembled into a cell with blocking electrodes on both sides according to the structure of steel sheet||separator||steel sheet for ion conductivity test.
[0171] The monomer prepolymer solution obtained in step (1) is mixed evenly with the electrolyte solution, and then injected into the first half cell and the second half cell respectively for infiltration, so as to fully infiltrate the positive electrode layer, the negative electrode layer and the separator layer; after standing at room temperature for 8 hours, the mixture is cured at 80°C for 24 hours, so that the mixture is solidified in situ inside the battery to form a polymer solid electrolyte.
[0172] (4) lithium iron phosphate (LiFePO4), conductive carbon black (Super-P) and binder polyvinylidene fluoride (PVDF) are weighed and mixed in a mass ratio of 97.8:0.7:1.5 to form a uniform positive electrode active material slurry, and the positive electrode active material slurry is coated on the surface of the positive electrode current collector aluminum foil, and after drying, cold pressing and die cutting, a positive electrode sheet is obtained;
[0173] The negative electrode material artificial graphite, conductive carbon black (Super-P), thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) are mixed in a mass ratio of 96.5:0.5:1.2:1.8 to form a uniform negative electrode active material slurry; the negative electrode active material slurry is coated on the surface of the negative electrode current collector copper foil, and after drying, cold pressing, and die cutting, a negative electrode active material layer is formed on the surface of the copper foil to obtain a negative electrode sheet;
[0174] A soft-pack laminated battery is prepared at an ambient dew point of ≤-45°C using a ceramic separator as a separator, and the positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the positive and negative electrode tabs on the same side, so that the separator is located between the positive and negative electrode sheets to play an isolating role, and a bare cell is obtained. The bare cell is placed in an aluminum-plastic film outer package, vacuum-baked at 90°C for 12 hours, cooled to below 40°C, and then injected with a mixture of the monomer prepolymer solution and the electrolyte solution obtained in step (1), followed by packaging, room temperature infiltration for 8 hours, 80°C curing for 24 hours, formation, aging, secondary vacuum packaging, and capacity division to obtain a battery for safety performance testing.
[0175] Comparative Example 4
[0176] (1) 1.56 g of vinyl acetate, 0.13 g of methyl ethyl ketone peroxide, and 0.56 g of polyethylene glycol methacrylate were mixed uniformly in a glove box filled with argon gas to obtain a flowing monomer prepolymer solution;
[0177] 0.17 g of lithium perchlorate and 0.05 g of lithium dioxalatoborate were uniformly mixed in 2.55 g of propylene carbonate to obtain an electrolyte solution;
[0178] (2) Lithium cobalt oxide (LiCoO2), conductive carbon black (Super-P) and binder polyvinylidene fluoride (PVDF) were mixed and ball-milled in a ratio of 96:2:2 for 20 hours, with NMP as the solvent and a solid-liquid ratio of 45%. The obtained slurry was coated on the surface of aluminum foil, dried with air at 110°C for 8 hours, and a 12 mm positive electrode disc was obtained by cutting; the positive electrode disc, polyethylene separator, and lithium sheet negative electrode were assembled into the first half cell according to the structure of positive electrode||separator||negative electrode for charge and discharge test; the steel sheet positive electrode, polyethylene separator, and steel sheet negative electrode were assembled into a battery with blocking electrodes on both sides according to the structure of steel sheet||separator||steel sheet for ion conductivity test.
[0179] After the monomer prepolymer solution obtained in step (1) is evenly mixed with the electrolyte solution, it is injected into the first half-cell and the second half-cell respectively for infiltration, so as to fully infiltrate the positive electrode layer, the negative electrode layer and the separator layer; after standing at room temperature for 7 hours, it is cured at 75°C for 24 hours to solidify the mixed solution in situ inside the battery to form a composite plastic crystalline polymer solid electrolyte.
[0180] (4) lithium cobalt oxide (LiCoO2), conductive carbon black (Super-P), binder polyvinylidene fluoride (PVDF) and conductive agent carbon nanotube (CNT) are weighed and mixed in a mass ratio of 97.0:1.2:0.8:1 to form a uniform positive electrode active material slurry, and the positive electrode active material slurry is coated on the surface of the positive electrode current collector aluminum foil, and after drying, cold pressing and die cutting, a positive electrode sheet is obtained;
[0181] The negative electrode material artificial graphite, conductive carbon black (Super-P), thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) are mixed in a mass ratio of 96.5:1:1.2:1.3 to form a uniform negative electrode active material slurry; the negative electrode active material slurry is coated on the surface of the negative electrode current collector copper foil, and after drying, cold pressing, and die cutting, a negative electrode active material layer is formed on the surface of the copper foil to obtain a negative electrode sheet;
[0182] A soft-pack laminated battery is prepared at an ambient dew point of ≤-45°C using a ceramic separator as a separator, and the positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the positive and negative electrode tabs on the same side, so that the separator is located between the positive and negative electrode sheets to play an isolating role, and a bare cell is obtained. The bare cell is placed in an aluminum-plastic film outer package, vacuum-baked at 90°C for 12 hours, cooled to below 40°C, and then injected with a mixture of the monomer prepolymer solution and the electrolyte solution obtained in step (1), followed by packaging, room temperature infiltration for 7 hours, 75°C curing for 24 hours, formation, aging, secondary vacuum packaging, and capacity division to obtain a battery for safety performance testing.
[0183] Comparative Example 5
[0184] (1) 1.56 g of vinyl acetate, 0.13 g of methyl ethyl ketone peroxide, and 0.56 g of polyethylene glycol methacrylate were mixed uniformly in a glove box filled with argon gas to obtain a flowing monomer prepolymer solution;
[0185] 1.11 g of N,N-diethylpyrrolidone bistrifluorosulfonyl imide, 0.17 g of lithium perchlorate, and 0.05 g of lithium dioxalatoborate were uniformly mixed in 1.44 g of propylene carbonate to obtain a plastic crystal electrolyte solution;
[0186] (2) Lithium cobalt oxide (LiCoO2), conductive carbon black (Super-P) and binder polyvinylidene fluoride (PVDF) were mixed and ball-milled in a ratio of 96:2:2 for 20 hours, with NMP as the solvent and a solid-liquid ratio of 45%. The obtained slurry was coated on the surface of aluminum foil, dried with air at 110°C for 8 hours, and a 12 mm positive electrode disc was obtained by cutting; the positive electrode disc, polyethylene separator, and lithium sheet negative electrode were assembled into the first half cell according to the structure of positive electrode||separator||negative electrode for charge and discharge test; the steel sheet positive electrode, polyethylene separator, and steel sheet negative electrode were assembled into a battery with blocking electrodes on both sides according to the structure of steel sheet||separator||steel sheet for ion conductivity test.
[0187] After the monomer prepolymer solution obtained in step (1) is evenly mixed with the plastic crystal electrolyte solution, it is injected into the first half-cell and the second half-cell respectively for infiltration, and the positive electrode layer, the negative electrode layer and the separator layer are fully infiltrated; after standing at room temperature for 7 hours, it is cured at 75°C for 24 hours to solidify the mixed solution in situ inside the battery to form a composite plastic crystal polymer solid electrolyte.
[0188] (3) lithium cobalt oxide (LiCoO2), conductive carbon black (Super-P), binder polyvinylidene fluoride (PVDF), and conductive agent carbon nanotube (CNT) are weighed and mixed in a mass ratio of 97.0:1.2:0.8:1 to form a uniform positive electrode active material slurry, and the positive electrode active material slurry is coated on the surface of the positive electrode current collector aluminum foil, and after drying, cold pressing, and die cutting, a positive electrode sheet is obtained;
[0189] The negative electrode material artificial graphite, conductive carbon black (Super-P), thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) are mixed in a mass ratio of 96.5:1:1.2:1.3 to form a uniform negative electrode active material slurry; the negative electrode active material slurry is coated on the surface of the negative electrode current collector copper foil, and after drying, cold pressing, and die cutting, a negative electrode active material layer is formed on the surface of the copper foil to obtain a negative electrode sheet;
[0190] A soft-pack laminated battery is prepared at an ambient dew point of ≤-45°C using a ceramic separator as a separator. The positive electrode, separator, and negative electrode are stacked in order, with the positive and negative electrode tabs on the same side, so that the separator is located between the positive and negative electrode sheets to play an isolating role, and a bare cell is obtained. The bare cell is placed in an aluminum-plastic film outer package, vacuum-baked at 90°C for 12 hours, cooled to below 40°C, and then injected with a mixture of the monomer prepolymer solution and the plastic crystal electrolyte solution obtained in step (1), followed by packaging, room temperature infiltration for 7 hours, 75°C curing for 24 hours, formation, aging, secondary vacuum packaging, and capacity division to obtain a battery for safety performance testing.
[0191] The batteries prepared in Examples 1 to 8 and Comparative Examples 1 to 5 were subjected to room temperature cycle performance tests, ion conductivity tests, and safety tests, and the test conditions were as follows:
[0192] (1) Room temperature cycle performance test: The prepared battery was charged at a constant current and constant voltage of 0.2C to the upper limit of the rated voltage in a constant temperature room at an ambient temperature of 25°C, with a cut-off current of 0.02C. After standing for 5 min, it was discharged at a constant current of 0.2C to the lower limit of the rated voltage. The cycle was repeated 200 times and the capacity retention rate was recorded. The capacity retention rate of the nth cycle (%) = (discharge specific capacity of the nth cycle / discharge specific capacity of the first cycle) * 100%.
[0193] (2) Room temperature rate discharge performance test: The prepared battery was charged at a constant current and constant voltage of 0.5C to the upper limit of the rated voltage in a constant temperature room with an ambient temperature of 25°C. The cut-off current was 0.02C. After standing for 5 minutes, it was discharged at a constant current of 0.5C until the voltage reached the lower limit of the rated voltage. The discharge capacity Q was recorded. 0.5C After standing for 5 minutes, charge at a constant current and voltage of 0.5C to the upper limit of the rated voltage, and the cut-off current is 0.02C. After standing for 5 minutes, discharge at a constant current of 3C to the lower limit of the rated voltage, and record the discharge capacity Q 3C , 3C discharge capacity retention rate η=Q 3C / Q 0.5C ×100%.
[0194] The upper and lower limits of the rated voltage of LFP batteries are: 2.5V ~ 3.65V; the upper and lower limits of the rated voltage of LCO batteries are: 3V ~ 4.45V;
[0195] (3) Ion conductivity test: The resistance of the prepared battery was tested by AC impedance using an electrochemical workstation, and the ionic conductivity was calculated using the following formula:
[0196]
[0197] Where, σ is the ionic conductivity (S / cm), t is the thickness of the polymerized electrolyte membrane (cm), R is the resistance (Ω), and S is the effective membrane area (cm 2 ).
[0198] (4) Needle penetration test: A needle penetration test is conducted on a safety testing machine. Specifically, a 5mm to 8mm high-temperature resistant steel needle (the cone angle of the needle tip is 45° to 60°, and the surface of the needle is smooth and free of rust, oxide layer and oil) is used to penetrate the battery at a speed of 25mm / s in a direction perpendicular to the large surface of the battery. The penetration position should be close to the geometric center of the punctured surface, and the steel needle stays in the battery. Observe for 1 hour to see if it catches fire.
[0199] The results are shown in Table 1, which shows the ionic conductivity and performance test results of the batteries provided in the examples and comparative examples of the present application.
[0200] Table 1 Performance test results of embodiments and comparative examples
[0201]
[0202] As can be seen from Table 1, without the effect of additives, the battery cycle retention rate, 3C rate discharge performance and safety performance of the composite plastic crystalline polymer solid electrolyte of the present invention are higher. Furthermore, the polymer solid electrolytes prepared using Examples 1 to 8 all showed higher ion conductivity and cycle retention rate than Comparative Examples 1 to 5, and safer needle puncture tests, indicating that the composite plastic crystalline polymer solid electrolyte of the present invention can effectively improve the battery cycle stability, ion conductivity and safety performance.
[0203] The above are only preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A polymer electrolyte, characterized in that The invention comprises 1wt% to 90wt% of a cross-linked polymer, 0.01wt% to 50wt% of a plastic crystal and 0.01wt% to 20wt% of a lithium salt; The plastic crystal is selected from 1-azabicyclo[2.2.2]octane and its derivatives.
2. The polymer electrolyte according to claim 1, characterized in that The plastic crystal is selected from at least one of 1-azabicyclo[2.2.2]octane perchloric acid, (R)-(-)-1-azabicyclo[2.2.2]octane-3-ol perchloric acid, (S)-(+)-1-azabicyclo[2.2.2]octane-3-ol perchloric acid and 1-azabicyclo[2.2.2]octane-3-ol perchloric acid; The cross-linked polymer is obtained by cross-linking and polymerization of a polymerization monomer, an initiator and a cross-linking agent; The lithium salt is selected from at least one of lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonic acid)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium chloride, lithium iodide, lithium bis(trifluoromethanesulfonic acid)imide and lithium hexafluoroarsenate.
3. The polymer electrolyte according to claim 2, characterized in that The polymerizable monomer is selected from at least one of vinylene carbonate, vinyl ethylene carbonate, vinyl carbonate, diethyl carbonate, triethylene glycol divinyl ether, methyl vinyl sulfone, ethyl vinyl sulfone, methyl methacrylate, pentafluoropropyl methacrylate, ethylene glycol dimethacrylate, propylene glycol dimethacrylate, n-butyl methacrylate, ethyl acrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, polyethylene oxide acrylate, polymethyl methacrylate, polyethylene glycol methyl ether methacrylate and polycyanoacrylate; The initiator is selected from azobisisobutyronitrile, azobisisoheptylnitrile, dimethyl azobisisobutyrate, benzoyl peroxide, lauroyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, methyl ethyl ketone peroxide, di-tert-butyl peroxide, lauroyl peroxide, diisopropylbenzene peroxide, N,N-dimethylcyclohexylamine, bis(2-dimethylaminoethyl) ether, triethylenediamine, triethylamine, N,N,N,N'-tetramethylalkylenediamine, N,N-dimethylbenzylamine, At least one of N,N-dimethylbutylamine, N,N-dimethylhexadecylamine, N,N-diethylpiperazine, N,N-diethyl-2-methylpiperazine, N,N'-bis(α-hydroxypropyl)-2-methylpiperazine, triethanolamine, N,N-dimethylethanolamine, N,N-dimethylpyridine, (dimethylaminoethyl) ether, N-methylethylenediamine, dimethylformamide, triethyleneethylenediamine, methyldiethyleneglycolamine, triethylenediamine and hexamethyldisilazane; The crosslinking agent is selected from at least one of polyethylene glycol diacrylate, polyethylene glycol methacrylate, polyethylene glycol dimethacrylate, tetra(ethylene glycol) diacrylate, pentaerythritol tetraacrylate, pentaerythritol glycidyl ether, 1,4-pyrazine dicarboxaldehyde, 4,4'-biphenyl dicarboxaldehyde, 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether, γ-glycidyl ether silyl propyl sesquioxane, trimethylolpropane triglycidyl ether, trimethylolpropane propoxy ester triacrylate, trimethylolpropane triacrylate and pentaerythritol tetraacrylate.
4. The method for preparing the polymer electrolyte according to any one of claims 1 to 3, comprising the following steps: Mixing the polymerization monomer, initiator and cross-linking agent uniformly to obtain a monomer prepolymer solution; The plastic crystal and the lithium salt are mixed uniformly in a solvent to obtain a plastic crystal electrolyte solution; the plastic crystal is selected from 1-azabicyclo[2.2.2]octane and its derivatives; The monomer prepolymer solution and the plastic crystal electrolyte solution are uniformly mixed, polymerized and cross-linked under heating conditions to obtain a polymer electrolyte.
5. The preparation method according to claim 4, characterized in that: The solvent is selected from at least one of ethylene carbonate, fluoroethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, butylene carbonate, methyl propyl carbonate, methyl formate, ethyl formate, propyl formate, butyl formate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, 8-valerolactone, tetrahydrofuran, 2-methyltetrahydrofuran, 4-methyl 1,3-dioxolane, 2-methyl-1,3-dioxolane, ethylene glycol dimethyl ether, 1,3-dioxolane, cyclopentane and dimethyl sulfoxide.
6. The preparation method according to claim 4, characterized in that: The mixed solution of the monomer prepolymer solution and the plastic crystal electrolyte solution includes: 1 wt% to 90 wt% of a polymerizable monomer; 0.01 wt% to 10 wt% of an initiator; 1 wt% to 90 wt% of a cross-linking agent; 0.01wt% to 50wt% plastic crystal; 0.01wt% to 20wt% of lithium salt, 0 to 60 wt% solvent.
7. A polymer solid-state battery, comprising a positive electrode, a negative electrode, a separator and an in-situ generated polymer electrolyte, wherein the polymer electrolyte comprises 1 wt% to 90 wt% of a cross-linked polymer, 0.01 wt% to 50 wt% of a plastic crystal and 0.01 wt% to 20 wt% of a lithium salt; The plastic crystal is selected from 1-azabicyclo[2.2.2]octane and its derivatives.
8. A method for preparing a polymer solid-state battery, comprising: Mixing the polymerization monomer, initiator and cross-linking agent uniformly to obtain a monomer prepolymer solution; The plastic crystal and the lithium salt are mixed uniformly in a solvent to obtain a plastic crystal electrolyte solution; the plastic crystal is selected from 1-azabicyclo[2.2.2]octane and its derivatives; The monomer prepolymer solution and the plastic crystal electrolyte solution are mixed and added into a battery consisting of a positive electrode, a negative electrode and a separator to form a polymer electrolyte in situ by polymerization and cross-linking.
9. The preparation method according to claim 8, characterized in that: The step of standing and soaking is also included before polymerization and cross-linking.
10. The preparation method according to claim 8, characterized in that: The polymerization cross-linking is carried out at a temperature of 30° C. to 120° C. and for a time of 2 h to 72 h.
Citation Information
Cited By
Elastic solid electrolyte with lithium ion selective transmembrane transmission characteristic and preparation method thereof
CN120319879A